Globalization and change in Asia - Rondinelli, Dennis A. (ed.); Heffron, John M. (ed.) (London, 2007)
Globalization and Change in Asia explores three decades of adjustment on the part of governments, civil society, and the private sector to the complex new forces of international competition. Recognizing that the benefits of globalization have not accrued equally to all Asian countries, nor to all stratums of society, the authors seek lessons that can help shape development policy to effect the greatest good. Thus, they focus on the essential ingredients of the most broadly successful globalization strategies - strategies that can most optimally respond to the economic, social, and technological challenges that lay ahead.
Keywords: Globalization-Asia